Gender Equality and Fulfillment of Human Rights in the Education System in Indonesia - M. Afiqul Adib; Nurwahidah Nurwahidah (Spiritus: Religious Studies and Education Journal, 2024)
This study aims to examine the role of gender equality and the fulfillment of human rights (HR) in building an inclusive and equitable education system in Indonesia. Gender equality and HR are fundamental principles that must be integrated into the education system to ensure equal access and quality of education for all students, regardless of gender, social background, or economic status. The focus of this research is to analyze national education policies related to gender equality and HR, as well as to identify the challenges faced in their implementation. This study employs a qualitative approach using document analysis methods. Data were collected through an in-depth review of national education policies, official government reports, and relevant academic literature. The findings reveal that although various policies and programs have been designed to promote gender equality and HR, their implementation still faces social, cultural, and structural barriers. Indonesia’s educational curriculum incorporates the principles of gender equality and HR, yet its application in practice remains suboptimal and requires further improvement. This research contributes strategically by recommending steps such as teacher training, the revision of more inclusive learning materials, and the implementation of consistent monitoring and evaluation systems. These measures are expected to strengthen educational policies to create a truly equitable education system. Ultimately, an inclusive system will positively impact social development and the overall progress of the nation.